Morphology of the immature stages of Cheilosia vernalis (Fallén, 1817) and an updated description of the larva of Cheilosia canicularis (Panzer, 1801) (Diptera: Syrphidae) - José J. Orengo-Green; Iván Ballester-Torres; Pablo Aguado-Aranda; María Ángeles Marcos-García; Leif Bloss Carstensen; Antonio Ricarte (European Journal of Taxonomy)
With almost 500 species, Cheilosia Meigen, 1822 (Diptera: Syrphidae) is the most diverse genus of hoverflies in the Palaearctic Region. The larval morphology and biology of over 40 species of Cheilosia are known, but only the description of the immatures stages of 28 species has been done. The known larvae of Cheilosia have a wide range of feeding modes, including mycophages, borers in roots and stems, leaf-miners, cambium and sap feeders, and saprophages. In this study, all three larval stages and puparium of Cheilosia vernalis (Fallén, 1817) are described. This species was confirmed based on morphological, DNA (i.e., 5′ end region of the Cytochrome c oxidase subunit I gene) and geographic evidence. Larvae of C. vernalis were found in the stems of Leucanthemun vulgare Lam. (Asteraceae), Matricaria chamomilla L. (Asteraceae), and Tripleurospermum inodorum (L.) Sch.Bip. (Asteraceae) in Denmark, and all the immature stages were studied by stereo microscopy and scanning electron microscopy. The larval head skeleton and chaetotaxy were also described and illustrated. In addition, a clarification to identify larvae of Cheilosia canicularis (Panzer, 1801) is provided, according to an updated description of their immature stages. To facilitate the species identification, a key to all known root and stem-boring larvae of Cheilosia is provided.